2014
DOI: 10.15760/trec.115
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the Green Lanes: Evaluating Protected Bike Lanes in the U.S.

Abstract: About Your Neighborhood 3. Over the past two years, changes to my neighborhood as a place for. . .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 0 publications
3
55
1
Order By: Relevance
“…The built environment must include safe infrastructure to facilitate nonmotorized transportation. A study of five U.S. cities found that bicycle ridership increased between 21 and 171% within one year of building protected bicycle lanes (57). Bicycle use and walking are much more common in other areas of the world.…”
Section: Trip Distance and Number Of Motorized Tripsmentioning
confidence: 99%
“…The built environment must include safe infrastructure to facilitate nonmotorized transportation. A study of five U.S. cities found that bicycle ridership increased between 21 and 171% within one year of building protected bicycle lanes (57). Bicycle use and walking are much more common in other areas of the world.…”
Section: Trip Distance and Number Of Motorized Tripsmentioning
confidence: 99%
“…The UK motorcyclist and equestrian studies reported drivers' concerns about vulnerable road user unpredictability, vulnerability, and law-breaking, all of which echo concerns voiced by drivers about bicyclists in previous research (Basford, Reid, Lester, Thomson, & Tolmie, 2002;Gatersleben & Haddad, 2010;Monsere et al, 2014).…”
Section: Attitudes In Travel Behavior Researchmentioning
confidence: 61%
“…were negative toward drivers, pedestrians, and bicyclists, but were significantly more negative toward bicyclists (Monsere et al, 2014). A survey of citizens in the UK probed respondents' attitudes about the behaviors, motivations, background, and personality they attribute to the "typical cyclist" (Gatersleben & Haddad, 2010).…”
Section: Attitudes In Travel Behavior Researchmentioning
confidence: 99%
See 2 more Smart Citations